2019
DOI: 10.1002/pen.25158
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and self‐healing behavior of thermoreversible epoxy resins modified with nitrile butadiene rubber

Abstract: Cracks may generate in epoxy resins, which can affect the comprehensive property and shorten service life. The problem is expected to be resolved by endowing epoxy resin with self‐healing performance. Herein, a new kind of self‐healing epoxy resin containing both Diels–Alder (DA) bonds and nitrile butadiene rubber (NBR) has been developed. The self‐healing performance and mechanical properties of as‐prepared epoxy resins are investigated by qualitative observation and quantitative measuring. Results reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…It was worth noting that a new peak at 1775 cm −1 presented in FA‐FGE‐BMI spectrum, and it was the characteristic absorption peak of DA adducts. [ 6 ] The results further showed that DA addition reaction took place successfully. As a result, adducts were introduced into the epoxy resin successfully.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…It was worth noting that a new peak at 1775 cm −1 presented in FA‐FGE‐BMI spectrum, and it was the characteristic absorption peak of DA adducts. [ 6 ] The results further showed that DA addition reaction took place successfully. As a result, adducts were introduced into the epoxy resin successfully.…”
Section: Resultsmentioning
confidence: 90%
“…The problem is expected to be solved by endowing epoxy resin with self-healing performance. [6][7][8][9] The self-healing property can be endowed by incorporating the dynamic covalent bonds into materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the particle size and dispersion of additives have a great influence on the physical properties of epoxy resin. Generally, the additive with a small particle size can cause higher physical and mechanical properties in EP [14,15]. Bao et al [16] used silicon-containing flame retardant (PMDA) to modify carbon nanotubes (CNTs), and the obtained modified CNTs showed better dispersion performance in epoxy resin, showing good flame retardancy and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Many recyclable elastomers based on non-covalent bonds (hydrogen bonding, [5,6] metal ion coordination bonding, [7] host-guest interactions [8] ) have been developed in the last decade. Compared to the noncovalent cross-linked network structure, such as instability and low mechanical strength, dynamically reversible covalent crosslinked (dynamic imine bonds, [9][10][11] disulfide bonds, [12,13] D-A bonds, [14,15] and acylamino-urea bonds [16] ) elastomers avoid these problems and make the elastomer dimensionally stable, high mechanical strength, solvent resistance.…”
Section: Introductionmentioning
confidence: 99%